An overview of the prevalence and distribution of gastrointestinal parasitic infections in post-war Iraq - Abdulhaleem, N; Mahmuda, A; Khadim, AKJ; Abd Majid, R; Lung, LTT; Abdullah, WO; Unyah, Z (Pharmacotherapy Group, 2024)
Indexed by WOS